Multipath and its manifestations in the real environment of geodetic practice - Jadviščok, Petr; Ovesna, Gabriela; Konečny, Miroslav (Geodesy and Cartography, 2016)
The paper is concerned with the negative manifestation of the multipath factor in application of the GNSS technology. It points to manifestations of the multipath effect in a specific situation of surveying practice. The evaluation is based on a model situation under intentionally deteriorated observational conditions by the presence of a building.